Gesljenje leposlovja in slovenske šolske knjižnice - Stubelj, Vilma (Šolska knjižnica, 2012)
"Hidden Treasure" was a research project supported by Ministry for Education, Science and Sport and aimed at improving the current subject description of fiction literary works. Active participants were library of secondary school Bežigrad, Public library Bežigrad and Department of Library and Information Science and Book Studies of Faculty of Arts Ljubljana. In December 2010, 105 out of 142 Slovene secondary school libraries were involved in a questionnaire which tried to establish whether Slovene secondary school librarians know about the project and use subject indexing as part of their work. 73% of librarians are not familiar with the project and 40% of them never do subject indexing of fiction. 62 libraries use Slovenian general list of subject headings (Slovene: Slovenski splošni geslovnik- SSG) and printed or online published Systematic tables of Universal decimal classification (Slovene: Tablice UDK) when adding subject headings in local catalogues. Subject headings mostly refer to the contents of a book; librarians form them by themselves considering users' needs. Most librarians (84%) add 2-5 subject headings for one bibliographic description; almost never they add a subject heading for their target audience and always one for genre. Students rarely look for books with subject headings, while librarians often do. Most librarians (44) find subject headings very important; however, in the future librarians should also approach library users in cooperation with other librarians and high school teachers.
Keywords: gesljenje; klasifikacija; leposlovje; projekti; srednje šole; šolske knjižnice